2022
DOI: 10.1186/s12879-022-07661-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection and enterovirus B: post EV-A71 mass vaccination scenario in China

Abstract: Background Hand, foot, and mouth disease (HFMD) is a common child infectious disease caused by more than 20 enterovirus (EV) serotypes. In recent years, enterovirus A71 (EV-A71) has been replaced by Coxsackievirus A6 (CV-A6) to become the predominant serotype. Multiple EV serotypes co-circulate in HFMD epidemics, and this study aimed to investigate the etiological epidemic characteristics of an HFMD outbreak in Kunming, China in 2019. Methods The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Viral RNA was extracted from stool suspensions by the Axygen Body Fluid DNA/RNA Miniprep Kit (Axygen) and directly tested by nested reverse transcription-polymerase chain reaction (nRT-PCR) using the primers B-OS/B-OAS, B-IS/B-IAS, and 222/224, AN88/AN89, respectively as previously described 8,10 (Supporting Information: Table S1). Most enterovirus species were resolved using a set of primers (224/222 and AN88/AN89) which is suitable for the screening of large samples.…”
Section: Amplification Of the Partial Vp1 Regions And Sequencingmentioning
confidence: 99%
See 3 more Smart Citations
“…Viral RNA was extracted from stool suspensions by the Axygen Body Fluid DNA/RNA Miniprep Kit (Axygen) and directly tested by nested reverse transcription-polymerase chain reaction (nRT-PCR) using the primers B-OS/B-OAS, B-IS/B-IAS, and 222/224, AN88/AN89, respectively as previously described 8,10 (Supporting Information: Table S1). Most enterovirus species were resolved using a set of primers (224/222 and AN88/AN89) which is suitable for the screening of large samples.…”
Section: Amplification Of the Partial Vp1 Regions And Sequencingmentioning
confidence: 99%
“…Given that they are not the predominant serotypes, there is rarely concern about EV‐Bs. However, some studies have found that EV‐Bs such as CV‐B1, CV‐B3, CV‐B4, and CV‐B5 may become important pathogens involved in HFMD 10–13 . At present, five distinct CV‐B4 genotypes (A–E) and four divergent CV‐B5 genogroups (A–D) have been identified, respectively 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a monovalent vaccine against Enterovirus-A71 (EV-A71), responsible for outbreaks of Hand, Foot and Mouth Disease, was approved by the China Food and Drug Administration [ 19 , 20 ]. Since introduction of the vaccine the amount of HFMD cases caused by EV-A71 has dropped markedly [ 21 ], leading to vaccine research into other HFMD-causing enteroviruses [ 22 , 23 , 24 , 25 ] to develop a multivalent HFMD vaccine. EV-D68, previously misclassified as HRV-87 [ 26 ], caused a major outbreak of respiratory disease associated with acute flaccid myelitis in 2014 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%